2002
DOI: 10.1007/s00109-002-0381-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SREBF-1a and SCAP polymorphisms on plasma levels of lipids, severity, progression and regression of coronary atherosclerosis and response to therapy with fluvastatin

Abstract: Sterol regulatory elements binding factor-1a (SREBF-1a) and SREBF cleavage activating protein (SCAP) regulate lipids homeostasis. Polymorphisms in SREBF-1a and SCAP could affect plasma levels of lipids and risk of atherosclerosis. We determined association of SREBF-1a -36del/G and SCAP 2386A/G genotypes with plasma levels of lipids, severity and progression/regression of coronary atherosclerosis, and response to treatment with fluvastatin in a well-characterized Lipoprotein Coronary Atherosclerosis Study popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 29 publications
0
28
1
1
Order By: Relevance
“…Despite of the relationship of SREBF1 -36delG and SCAP A2386G polymorphisms on serum lipids in response to fluvastatin and simvastatin reported previously [17,18], we did not find significant association between these variants and response to atorvastatin. These results are suggestive that polymorphisms in SREBF1 and SCAP may play a minor role in determining the pharmacological response to statins.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite of the relationship of SREBF1 -36delG and SCAP A2386G polymorphisms on serum lipids in response to fluvastatin and simvastatin reported previously [17,18], we did not find significant association between these variants and response to atorvastatin. These results are suggestive that polymorphisms in SREBF1 and SCAP may play a minor role in determining the pharmacological response to statins.…”
Section: Discussioncontrasting
confidence: 99%
“…SREBF1 gene has an indel polymorphism in the promoter region (-36del/G) that was associated with an atherogenic lipid profile and increased risk for cardiovascular disease [16]. SREBF1 -36delG variant was also related to variation on plasma apoA-I in response to fluvastatin [17] but not simvastatin [18]. A common polymorphism of the SCAP gene (A2386G, Ile796Val), located at its carboxyl terminal domain that interacts with SREBP1 [19], was found to be a significant predictor of cholesterol and triglyceride responses to simvastatin [18], but not to pravastatin therapy [20].…”
Section: Introductionmentioning
confidence: 99%
“…23 Considering this finding and the strong LD in the region around SREBF1 on 17p11.2, it is possible that the association observed with the RAI1 marker is actually picking up signal from a SREBF1 variant, or vice versa. In dbSNP (http:// www.ncbi.nlm.nih.gov/projects/SNP/) and the scientific literature, several SNPs have been reported to change the amino acid composition of SREBP1 or to influence the level of cholesterol synthesis, [24][25][26] but none of these SNPs are deposited in HapMap and we have therefore not been able to conclude on their LD to the associated SNPs of the present study. The SREBF2 gene is located on chromosome 22q13.2.…”
Section: Discussionmentioning
confidence: 84%
“…13,14 In one study, Salek et al 13 reported the effect of SCAP and SREBF-1a polymorphisms on hypolipidemic response to fluvastatin treatment. In that investigation, they found a significant genotype-treatment interaction between SREBF-1a polymorphism and changes in apolipoprotein (apo) A-I, apo C-III and HDL-C levels, but did not find any association with SCAP genotypes.…”
Section: Characteristics Of the Population Studymentioning
confidence: 99%